Inflation Targeting and the Unemployment-Inflation Trade-off - Wong, Chorng-Huey (IMF Working Papers; Working Paper, 2001)
This paper examines the impact of the introduction of inflation targeting on the unemployment-inflation trade-off in OECD countries. Theoretical models suggest that the credibility-enhancing effects of the adoption of inflation targeting should cause an improvement in the unemployment-inflation trade-off, id est, that reducing inflation by a given amount should occur with a smaller rise in unemployment. The empirical evidence examined for OECD countries adopting inflation targeting supports this hypothesis. Using a smooth transition regression model, it is shown that the improvement in this trade-off does not take place immediately after the adoption of inflation targeting; rather, it improves over time as the credibility of the central bank is established.